Solve for z
z=-\frac{6}{53}+\frac{21}{53}i\approx -0.113207547+0.396226415i
Share
Copied to clipboard
z\left(-3+4i\right)+5iz-2z+3i+3=0
Use the distributive property to multiply z by 5i-2.
z\left(-3+4i\right)+\left(-2+5i\right)z+3i+3=0
Combine 5iz and -2z to get \left(-2+5i\right)z.
\left(-5+9i\right)z+3i+3=0
Combine z\left(-3+4i\right) and \left(-2+5i\right)z to get \left(-5+9i\right)z.
\left(-5+9i\right)z+3=-3i
Subtract 3i from both sides. Anything subtracted from zero gives its negation.
\left(-5+9i\right)z=-3i-3
Subtract 3 from both sides.
\left(-5+9i\right)z=-3-3i
The equation is in standard form.
\frac{\left(-5+9i\right)z}{-5+9i}=\frac{-3-3i}{-5+9i}
Divide both sides by -5+9i.
z=\frac{-3-3i}{-5+9i}
Dividing by -5+9i undoes the multiplication by -5+9i.
z=-\frac{6}{53}+\frac{21}{53}i
Divide -3-3i by -5+9i.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}